Clinical evaluation of Brinaldix. A new oral diuretic. Issue 474 (April 1965) - Briggs, J. D.; McSween, R. N.; Kennedy, A. C.
Abstract : 'Brinaldix', a new non-thiazide oral diuretic, has been used in a trial on three normal subjects and fourteen patients with oedema from various causes. It is a potent salidiuretic and proved superior to bendrofluazide in 10 out of 14 patients. It produced a substantial potassium diuresis, and we are of the opinion that potassium supplements should be given in conjunction with it. In one normal subject it produced a period of postural hypotension; no other major side-effects were noted.